Integrating ORAI Application in Teaching English at Senior High School - Halimah Halimah; Jauhar Helmie; Nuraeni Susulawati (IJET (Indonesian Journal of English Teaching), 2018)
As an English teacher in the era of industrial revolution 4.0 it is hoped that a teacher is able to apply any kinds of teaching media to create the teaching and learning atmosphere joyfully and to support in gaining the teaching and learning objectives effectively. There are numerous teaching media based on technology. One of them is Orai Application that is applied in teaching and learning of English especially speaking fluency. Today, all graduates face a world transformed by technology, in which the Internet, cloud computing, and social media create different opportunities and challenges for formal education systems. Higher education in the fourth industrial revolution is a complex, dialectical and exciting opportunity which can potentially transform society for the better. The fourth industrial revolution is powered by artificial intelligence and it will transform the workplace from tasks based characteristics to the human centred characteristics. This paper is aims to explore the use of Orai application in classroom teaching speaking in assisting student’s speaking fluency.